Características en la producción del habla en niños de 6 a 7 años con frenillo lingual alterado de la IE Liceo Naval "Almirante Guise". - Fajardo Perry, Nora Ynés (2014)
The following is a simple descriptive study, whose main objective is to determine the features in speech production in children aged 6 to 7 with a lingual frenulum alteration. To collect data we used the Tongue Frenulum Evaluation Protocol of Irene Marchesan and the systematic observation technique, in order to classify different lingual frenulum types, as well as identify the characteristics in the speech production to a population of 109 children aged 6 to 7 years of the school Liceo Naval Almirante Guise, in the district of San Borja.During this process a photographic and video recordwas carried out. The results of the study show that 88% of the studied population, presented a normal lingual frenulum and 12% (13 children) presented altered lingual frenulum. The most frequent alterations were a short frenulum for 5.50% of cases, followed by the short with anterior insertion, in 4.59% and the anterior insertion on 1.83% of the cases. Of the from children who show altered lingual frenulum, 77% present speech disorders, being the more frequent distortions (76.92%), followed by substitutions (46.15%) and omissions (38.46%). The speech sounds which presented alterations in their production were /r/, /ɾ / and their consonant clusters. Altered frenulum that cause problems are the short lingual frenulum and the short with anterior insertion. These problems include speech disorders, alteration in the tongue tip (apex) during their elevation and the proper performance of tongue mobility